1981
DOI: 10.1073/pnas.78.1.606
|View full text |Cite
|
Sign up to set email alerts
|

Vertical transmission of susceptibility to stuttering with sex-modified expression.

Abstract: Stuttering is not usually considered genetic, although it has long been known to be familial. Data collected on 2035 relatives of397 unrelated adult stutterers confirm and quantify the strong familial concentration. Our analytic approach to these family data, one that does not require specification of a genetic hypothesis, shows that stuttering among relatives occurs in a pattern indicating vertical transmission ofa susceptibility to stuttering with sex-modified expression. Although simple Mendelian hypotheses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

1981
1981
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(27 citation statements)
references
References 6 publications
3
23
0
1
Order By: Relevance
“…Though, initially all were viewed as nonstutterers, follow-up a year later revealed that 26 were then regarded as stutterers. This finding is consistent with the genetically based high-risk hypothesis that has been proposed over the years in relation to children o f stutterers (An drew and Harris, 1964; Van Praag and Janssen, 1980;Kidd, 1977;Kidd et al, 1981), O f those children who came to be seen as stutterers, 16 were male and 10 were female. This yielded a male-to-female ratio o f 1.6:1, which is larger than that found by Yairi (1983) in a younger group o f stuttering children (1.2:1) but smaller than the estimated 4:1 ratio among adult stut terers (Bloodstein, 1987).…”
Section: Discussionsupporting
confidence: 80%
“…Though, initially all were viewed as nonstutterers, follow-up a year later revealed that 26 were then regarded as stutterers. This finding is consistent with the genetically based high-risk hypothesis that has been proposed over the years in relation to children o f stutterers (An drew and Harris, 1964; Van Praag and Janssen, 1980;Kidd, 1977;Kidd et al, 1981), O f those children who came to be seen as stutterers, 16 were male and 10 were female. This yielded a male-to-female ratio o f 1.6:1, which is larger than that found by Yairi (1983) in a younger group o f stuttering children (1.2:1) but smaller than the estimated 4:1 ratio among adult stut terers (Bloodstein, 1987).…”
Section: Discussionsupporting
confidence: 80%
“…These observations point to a genetic factor. Research by Howie (1981) and Kidd and associates at Yale (Kidd, 1980;Kidd, 1984;Kidd, Heimbuch, & Records, 1981) added much knowledge about the role of genetics in the transmission of susceptibility to stuttering. The Yale studies' findings were consistent with a polygenic multifactorial model of inheritance with a possible major locus, and with males having a higher susceptibility.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…When the monozygotic and dizygotic twin correlations are used to model the additive genetic and environmental components, both Andrews et al (1991) and Felsenfeld et al (2000) concluded that approximately 70% of the phenotypic variance is due to additive genetic effects and approximately 30% to non-shared effects. Several studies have shown a higher incidence of stuttering in first degree relatives (20-74%) than in the general population (1.3-42%) (Kidd, Heimbuch, & Records, 1981;Yairi, Ambrose, & Cox, 1996). Both the concordance of stuttering among monozygotic twin pairs and the familial aggregation of stuttering are consistent with a genetic component to stuttering.…”
Section: Introductionmentioning
confidence: 99%